Association Between Body Mass Index, Visceral Fat, and the Risk of Metabolic Syndrome Among Obese Adolescents in Indonesia - Ataillah Azizah Indriati; Nur Aisiyah Widjaja; Meity Ardiana; Meta Herdiana Hanindita (Journal La Medihealtico, 2025)
This study examined the association between Body Mass Index (BMI) and visceral fat with the risk of Metabolic Syndrome (MetS) among obese adolescents in Surabaya and Sidoarjo, Indonesia. The research addressed the increasing burden of cardiometabolic disorders in adolescents, focusing on the importance of early screening for central adiposity. A cross- sectional design was employed involving 72 obese adolescents from junior and senior high schools. BMI was measured using standard anthropometry, while visceral fat was assessed through Waist Circumference (WC)and Bioelectrical Impedance Analysis (BIA). MetS was identified based on established clinical criteria. The findings revealed that both BMI and visceral fat were significantly associated with MetS, with BIA-derived visceral fat demonstrating the strongest predictive value. Adolescents with high visceral fat exhibited substantially higher risks of dyslipidemia, hypertension, and overall metabolic abnormalities. These results highlight the limitations of BMI as a standalone indicator and reinforce the need for integrating visceral fat assessment in school-based screening programs. Early identification and targeted interventions are essential to mitigate the progression of MetS during adolescence.